2014
DOI: 10.15640/jmpp.v2n3a1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Management Problem-Solving Processes through the Application of Emotional Intelligence Skills

Abstract: Purpose: Little research has been contributed to how the behaviors associated with emotional intelligence may be practically applied to enhance both individual and group management problem-solving. The purpose of this paper is to identify practical approaches to the application of emotional intelligence to the complexity of the management problem-solving process. These practical approaches are designed to instruct and aid problem solvers in the utilization of emotional intelligence skills to improve management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…When literature is examined in the literature, it has been found that problem-solving skills are related to emotional intelligence level, anger experience and critical thinking skills. Studies in people's emotional intelligence level increases problemsolving skills in the observed increase in (Deniz, 2013;Hess and Bacigalupo, 2014;İşmen, 2001;Shahbazi vd. 2014;Tetik ve Açıkgöz, 2013;Yılmaz Karabulutlu vd., 2011), constant anger problem solving skills with the confidence and positive self-control subscale, which is in inverse relationship with the approach-avoidance subscale (Aydın vd., 2005), found a positive and moderately significant relationship between problem-solving skills and critical thinking skills .…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When literature is examined in the literature, it has been found that problem-solving skills are related to emotional intelligence level, anger experience and critical thinking skills. Studies in people's emotional intelligence level increases problemsolving skills in the observed increase in (Deniz, 2013;Hess and Bacigalupo, 2014;İşmen, 2001;Shahbazi vd. 2014;Tetik ve Açıkgöz, 2013;Yılmaz Karabulutlu vd., 2011), constant anger problem solving skills with the confidence and positive self-control subscale, which is in inverse relationship with the approach-avoidance subscale (Aydın vd., 2005), found a positive and moderately significant relationship between problem-solving skills and critical thinking skills .…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Yapılan çalışmalarda kişilerin duygusal zeka düzeyi arttıkça problem çözme becerilerinde artış gözlendiği (Tetik ve Açıkgöz, 2013;İşmen, 2001;Deniz, 2013;Shahbazi vd. 2014;Hess and Bacigalupo, 2014;Yılmaz Karabulutlu vd., 2011), sürekli öfkenin problem çözme yeteneğine güven ve kişisel kontrol alt boyutu ile olumlu, yanaşma-kaçınma alt boyutu ile ters ilişki içinde olduğu (Aydın vd., 2005), problem çözme becerileri ile eleştirel düşünme becerileri arasında pozitif yönde ve orta düzeyde anlamlı bir ilişki olduğu bulunmuştur .…”
Section: Introductionunclassified
“…This shows that metacognitive awareness is important in the problem-solving process. Hess & Bacigalupo (2014) also stated that student awareness is very supportive of the process of solving problems. In addition to getting information, students also do not realize that the completion process they are working on is wrong.…”
Section: Introductionmentioning
confidence: 99%